2013
DOI: 10.1007/s00534-012-0592-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic liver resection for treating recurrent hepatocellular carcinoma

Abstract: Postoperative morbidity has been decreased by the introduction of laparoscopic liver resection in patients with recurrent HCC after curative hepatic resection. As a result, the duration of the postoperative stay is shorter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 15 publications
(13 reference statements)
5
68
0
Order By: Relevance
“…Belli et al, [13] Hu et al, [15] and Kanazawa et al [22] reported 12, 6, and 20 cases, respectively. They all concluded that repeat LLR for recurrent HCC in cirrhotic patients is a safe and feasible procedure.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Belli et al, [13] Hu et al, [15] and Kanazawa et al [22] reported 12, 6, and 20 cases, respectively. They all concluded that repeat LLR for recurrent HCC in cirrhotic patients is a safe and feasible procedure.…”
Section: Discussionmentioning
confidence: 95%
“…Belli et al [13] reported that the surgical time for repeat LLR was shorter and the adhesiolysis was easier for patients previously treated using LLR compared to open LR (OLR), and also detailed the advantages of the minimally invasive approach for managing the chronic oncologic sequelae of cirrhosis. Kanazawa et al [22] compared repeat LLR to repeat OLR in n = 20 groups of patients and concluded that postoperative morbidity and the duration of postoperative hospitalization have been decreased by the introduction of LLR for patients with recurrent HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the lack of prospective randomized controlled trials of laparoscopic hepatectomy for HCC, some studies based on matched comparisons reported short-term advantages in terms of blood loss, postoperative morbidity and similar long-term outcomes after laparoscopy compared with open hepatectomy [48,49,50,51,52]. For treatment of HCC in patients with liver cirrhosis, our previous study revealed postoperative morbidity, such as surgical site infection and intractable ascites, decreased by the induction of laparoscopic hepatectomy, and the necessity for invasive treatment of postoperative complications decreased and the duration of postoperative hospitalization was shortened [51] (table 1).…”
Section: Laparoscopic Hepatectomy For Hccmentioning
confidence: 99%